Divorce for Sirri Marriage Carried Out by Kairatu West Seram Community - Angga, La Ode; Ruslan, Dyah Auliah Rachma; Baharuddin, Wahdaniah; Amsyahrun, La Ode Amir; Ipaenin, Muhammad Haz Reza (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Marriage is said to be valid according to law if it is carried out according to the laws of each religion and belief, otherwise the marriage must be recorded according to applicable laws and regulations.Purposes of the Research: the specific purposse of this research are: 1. To find out and analyze the basis for allowing the implementation of Sirri Marriage in Kairatu Village community, and 2. To find out and analyze legal implication of Sirri Marriage implementation in Kairatu Village community.Methods of the Research: This research was conducted using empirical juridical approach which is a study of descriptive qualitative analysis. This research tried to study the Implementation and legal consequences of Sirri marriage in Kairatu Village, West Seram, Maluku Province. How the empirical juridical or sociological juridical method works in this research proposal is; first, the results of collecting and discovering data and information obtained by literature study of the basic assumptions or assumptions are used to answer the problems in this research. Then, inductive-verification testing is carried out on current facts existed within the community. Hence, the truth in a research is declared reliable without having to go through rationalization process.Results of the Research: Marriage can be said to be legally valid if it is carried out according to the trust of the bride and groom and registered with the marriage registration officer. For those who are Muslim, they are registered with the Office of Religious Affairs, while for those who are non-Muslim, they are registered with the civil registry office.